2007
DOI: 10.1085/jgp.200609612
|View full text |Cite
|
Sign up to set email alerts
|

The Role of S4 Charges in Voltage-dependent and Voltage-independent KCNQ1 Potassium Channel Complexes

Abstract: Voltage-gated potassium (Kv) channels extend their functional repertoire by coassembling with MinK-related peptides (MiRPs). MinK slows the activation of channels formed with KCNQ1 α subunits to generate the voltage-dependent IKs channel in human heart; MiRP1 and MiRP2 remove the voltage dependence of KCNQ1 to generate potassium “leak” currents in gastrointestinal epithelia. Other Kv α subunits interact with MiRP1 and MiRP2 but without loss of voltage dependence; the mechanism for this disparity is unknown. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 37 publications
9
127
0
Order By: Relevance
“…The S4 charge neutralization mutant R243A was previously shown to shift to more depolarized potentials and decrease the slope of the G(V) curve for KCNQ1 (14). We tested the hypothesis that the fluorescence signal, if it reports the movement of the voltage sensor, would change in a similar manner for this mutation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The S4 charge neutralization mutant R243A was previously shown to shift to more depolarized potentials and decrease the slope of the G(V) curve for KCNQ1 (14). We tested the hypothesis that the fluorescence signal, if it reports the movement of the voltage sensor, would change in a similar manner for this mutation.…”
Section: Resultsmentioning
confidence: 97%
“…To date, no gating current measurements have been reported for KCNQ1 channels, likely due to the low valence and slow movement of the KCNQ1 voltage sensor relative to other voltage-gated potassium channels (13,14). Previous efforts to characterize the KCNQ1 voltage sensor in the presence and absence of KCNE1 relied on cysteine accessibility studies, and although they were able to gain insights into the movements of the voltage sensor, they provide only a limited view of its behavior (15,16).…”
Section: Embers Of the Superfamily Of Voltage-gated Cation Channelsmentioning
confidence: 99%
“…To more rigorously address the possibility that KCNQ1 channels can open before all four voltage sensors move, we explore another voltage sensor mutation, R231C, which leads to a constitutively active channel by locking the voltage sensor in the activated position (20,21). Again, using coexpression, we explore whether the presence of constitutively active voltage sensors within a coassembled channel of KCNQ1 and KCNQ1 R231C subunits generates voltage-independent (constitutive) current.…”
Section: Resultsmentioning
confidence: 99%
“…4, smaller delay in the mutants could be due to other reasons, for example, faster transition from the downstate to the pre-upstate. ARTICLE There have been several mutation studies on the S4 segment, mainly focusing on the role of the positively charged residues [30][31][32][33]43 . Wu et al 33 have shown that mutations on the first arginine (R1; Arg228) and the second arginine (R2; Arg231) of the S4 segment destabilize the closed state and mutations on the fourth arginine (R4; Arg237) and the six arginine (R6; Arg243) destabilize the open state.…”
Section: Discussionmentioning
confidence: 99%